The Effect of Motivation and Work Environment on Employee Performance of PT. Bivouac Outdoor Equipment Bandung - Laraswati, Ratna; Shinta Oktafien, (Technium Social Sciences Journal, 2020)
This study aims to determine how motivation and work environment to the performance of employees of PT. Bivouac Outdoor Equipment Bandung, as well as to find out how much influence Motivation and Work Environment on Employee Performance at PT Bivouac Outdoor Equipment Bandung, either partially or simultaneously. The research method used in this research is descriptive calculation method and verification method. As for the population is all employees of PT. Bivouac Outdoor Equipment, amounting to 50 people with the same number of samples as the population because the number of population is less than 100 people. The results showed that the motivation was considered good and the work environment was considered good. Simultaneously, Motivation and Work Environment affect Employee Performance at PT Bivouac Outdoor Equipment Bandung.